MODEL GOOD CORPORATE GOVERNANCE UNTUK KEBERLANJUTAN BIDANG USAHA MILIK PONDOK PESANTREN : Studi Kasus Pondok Pesantren Salafiyah Syafiiyah Sukorejo Situbondo - M. Zikwan; Ahmad Hamdi (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2026)
This study aims to analyze the implementation of Good Corporate Governance (GCG) in supporting the sustainability of Pesantren-Owned Business Units (BUMP) at Salafiyah Syafi’iyah Islamic Boarding School, Sukorejo Situbondo. The research employs a qualitative approach with a case study design, using observation, in-depth interviews, and documentation as data collection techniques. Data analysis was conducted using the constant comparative method and Miles and Huberman’s model. The findings reveal that the BUMP structure follows a semi-decentralized pattern with a coordinative approach. BUMP does not function as a centralized controlling entity but rather as a coordinating body that connects various business units with operational autonomy. The implementation of GCG principles—transparency, accountability, responsibility, professionalism, and fairness—has been carried out substantively, though in a contextual manner aligned with pesantren values. Transparency is reflected in periodic reporting, accountability in clear task distribution, and responsibility in the orientation toward sustainability and communal benefit. Furthermore, the governance model is categorized as a value-based coordinative-participatory model, integrating modern GCG principles with Islamic values such as trust (amanah), collectivity, and moral responsibility. This model effectively balances operational flexibility with institutional alignment, thereby enhancing the sustainability, adaptability, and competitiveness of pesantren-based enterprises..